PENGEMBANGAN PARIWISATA BERBASIS MASYARAKAT (COMMUNITY BASED TOURISM) DALAM PEMBERDAYAAN MASYARAKAT (Studi kasus di Desa Bedulu, Blah Batuh, Gianyar) - I Wayan Pantiyasa (Jurnal Ilmiah Hospitality Management, 2011)
Development of tourism pattern known as the "Community Base Tourism" is the tourism development around the tourist activity takes place and mingle with the rural communities. The added value gained from the development of community-based tourism / rural are (1) the rural population can serve as actors, they can provide shelter for tourists, provision of food and beverages, laundry services, business services transportation, and other services. (2) Increasing consumption of local products (vegetables, fruits, crafts, traditional foods, and others, working sethingga will drive business continuity and locality-based tradition. (3) Encourage the empowerment of local labor, such as the provider of the art attraction culture, crafts, etc.). (4) increasing public awareness of the values and traditions of local culture and unique natural environment dimiliki.Strategi community-based Tourism Development in the Village Bedulu viewed from several aspects of the management organization, Profile of Tourists visiting, Perception of tourists who stay on the Service, Perception travel agents to tourist Bedulu village management, Participation / community-based Tourism. developing support can empower rural communities so as to improve the welfare of villagers.